Fernández Liesa, Carlos; Oliva Martínez, J. Daniel y Pérez de La Fuente, Óscar (ed.). Inflación y Deflación normativa. N.º 1 Colección Gregorio Peces-Barba, Dykinson, Madrid, 2022, 144 pp. (Anuario Español de Derecho Internacional, 2023)
Book Review